POLA PENDIDIKAN ANAK WANITA PEKERJA SEKTOR INFORMAL DJ KOTA YOGYAKARTA - Suwarna, Suwarna (Jurnal Cakrawala Pendidikan, 2016)
The pwpose of this research is to describe the educational pattern of children by women labor ofthe infonnal sector·in Yogyakarta municipality. The subjects of this research are wotnen labor of the infonnal sector at Maliboro Street, Yogyakarta. This research is the survei research. The instrument used in this research is a questionare, an observation sheet, and an interview question list. Data are analysed by using a descriptive technique. Based on the analysis, it shows that: (1) why the women work in the infonnal sector is aimed at helping their husband for making a living (55%) and seeking their children's education cost (45%). (2) The women who cany out the infonnal education pattern can be categorized in two namely good (36.55%) and poor (63.45%). (3) The women who support the fonnal education pattern can be explained that the good categoty is 61.33%, while tIle poor categol)' is 38.67%. (4) The women.who support the nonfonnal education pattern can be categorized ina two namely good category (11.83%) and poor category (88.17%). This can concluded that women labor of the infonnal sector in to educate the children tend to believe the fonnal education, while for the infonnal and non-fonnal education they lacked attention. (5) The main problems faced in their children's education is that the mother have no time to educate the children. This leads lack of togetherness, lack of intimacy, free relationship, and stubbron. The other problems are that education cost is very limited, the mothers Jack helping student's handle the subjects provided, and the children tend to believe the other people.